HUMORS RELATED TO CULINARY LABELS IN INSTAGRAM - Natasha Aprila (STBA Prayoga Padang, 2021)
Abstract The research was aimed to analyze the functions and types of humor Indonesian culinary entrepreneurs tend to use in writing their culinary labels. Humor onwriting and pronunciation of culinary labels is very easy to remember and will arise the curiosity of anyone who reads the culinary labels and wants to try themenu for sale in a culinary place. Therefore, this research analyzed the humor contained in the culinary labels on Instagram because nowadays some peopleuse social media as a means of promoting their business. Based on the research objectives above, the writer used qualitative research methods to collect andanalyze data. In this study, the writer found three functions of humor, which are humor to entertain, humor to criticize or ridicule, and humor to convey popularthings. Based on these findings, the writer concludes that the function of humor to entertain is one of the functions of humor that is often used in writing culinary labels. The writer hopes that the readers can develop the language by using humor language to develop linguistic language and also to improve the culinary business.